The Effect Of Punishment On Employee Productivity In Pt. Asuransi Bintang TBK Makassar Branch - ., Nurlina; Ramli, Anwar (Archives of Business Research, 2020)
This study aims to determine the magnitude of the influence of Punishmant on employee productivity at PT. Asuransi Bintang Tbk. Makassar branch. The population in this study were all employees of PT. Asuransi Bintang Tbk. Makassar branch, amounting to 25 people. The number of samples used was 25 people using saturated sample toeri. Data collection was carried out using interview, observation and questionnaire methods. The data analysis technique used is simple regression analysis using Statistical Product Standard Solution (SPSS) for window. This shows that punishment has a significant effect on employee work productivity at PT. Asuransi Bintang Tbk. Makassar branch.